Expression and prognostic significance of kallikrein-related peptidase 8 protein levels in advanced ovarian cancer by using automated quantitative analysis - Kountourakis, Panteleimon; Psyrri, Amanda; Scorilas, Andreas; Markakis, Sonia; Kowalski, Diane; Camp, Robert L.; Diamandis, Eleftherios P.; Dimopoulos, Meletios A. (Thrombosis and Haemostasis, 2009)
Kallikrein-related peptidases, a subgroup of the serine protease enzyme family, are considered to be important prognostic biomarkers in cancer. In this study we sought to determine the prognostic value of kallikrein-related peptidase 8 (KLK8,hK8,KLK-8) in ovarian cancer using a novel method of compartmentalised in situ protein analysis. A tissue array composed of 150 advanced stage ovarian cancers, uniformly treated with surgical debulking followed by platinum-paclitaxel combination chemotherapy, was constructed. For the evaluation of kallikrein-related peptidase 8 protein expression, we used an immunofluorescence-based method of automated in situ quantitative protein analysis (AQUA). Mean follow-up time of the cohort was 34.35 months. One hundred twenty-six of 150 cases had sufficient tissue for AQUA analysis. There were significant correlations between tumour mask KLK8 protein expression levels and clinicopathological variables, including grade (p=0.0011), residual disease (p=0.0063) and clinical response to chemotherapy(p=0.0346). In univariate survival analysis there was a significant correlation between KLK8 tumour mask expression and five years progression-free survival, meanwhile it was not associated with five-year overall survival (p =0.0694). Specifically, low KLK8 expression correlated with better outcome (top vs. bottom quartile, p=0.0319). In multivariate survival analysis, adjusting for well-characterised prognostic variables, tumour KLK8 expression level retained its prognostic significance for progression-free survival (95%CI: 0.341–1.027, p=0.045). The possibility that KLK8 may be a suitable candidate as a diagnostic and prognostic marker warrants further investigation.
Keywords: Kallikrein-related peptidase 8; AQUA; advanced ovarian cancer; prognosis